Kreasi dan Inovasi COMUT (Coklat Temulawak Imut) Penambah Nafsu Makan - Lina Puspitasari (LPPM Akbid Harapan Ibu Pekalongan, 2020)
Decreased appetite is a health problem that often occurs especially in children. Various ways of being taken by parents to solve the problem, either through drugs or pharmacology and nonfarmochology in the form of herbal-banquets based Temulawak. Temulawak is one of the spices produced in Cilacap regency that has not been utilized optimally. During this time, Temulawak is processed in a form of powder and made in beverage packaging. Temulawak Chocolate is an innovation that we develop to utilize Temulawak while addressing health problems in the form of decreased appetite. Because if the problem is not handled immediately, it can result in less nutrition or even poor nutrition. COMUT (cute Temulawak chocolate) is an innovation that we have developed to address the problem. The goal of community service is to implement COMUT in children and toddlers in PAUD Amanah Cilacap as an effort to increase appetite. The method used is a pretests post test one group, measuring the appetite level using the quesioner before and after given treatment of chocolate Temulawak. The results of community service is a change of appetite between before being given Temulawak chocolate and after given Temulawak chocolate. The result of Quesioner counting of 30 samples showed that the average score before given the Temulawak chocolate amounted to 29.4 and after the average COMUT was given to 35.1. As for the development of food from a portion of rata2 increases and snacks increase.